PENGARUH LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO DENGAN INKLUSI KEUANGAN SEBAGAI VARIABEL INTERVENING - Febriyanti, Fina; Sari, Lita Permata; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze and examine the effect of Financial literay on Financial behavior of Student o the Faculty of Economics and Business Abdurahman Saleh Situbondo with Finacial inclusion as an InterveningVariabel. The population in this study were all students of Faculty of Economics and Business. Data analysis and hypothesis testing inthis study used the Structura Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 appication show that Financial literacy has a significant effect on Financial inclusion.Financial literacy has a significant effect on Financial behavior. Financial inclusion has a significant effect on Financial behavior. The result of the indirect effect hypothesis test show that Financial literacy on Financial behavior through Financial inclusion hasa significant effect.